PENGARUH TIME BUDGET PRESSURE, PENGALAMAN KERJA, DAN KOMITMEN PROFESIONAL PADA PENGAMBILAN KEPUTUSAN ETIS KONSULTAN PAJAK DI PROVINSI BALI - Ni Made Putri Dwi Yanti; Anak Agung Ketut Agus Suardika (UNHI Press, 2020)
Tax Consultant is one of the accounting professions that often experiences ethical dilemmas in carrying out his profession. This study aims to determine the effect of time budget pressure, work experience, and professional commitment to the ethical decision making of Tax Consultants in Bali Province. The population in this study were all Tax Consultants in Bali Province, while 149 people were selected as research objects (samples). The sampling technique uses a purposive sampling method. The results showed that the time budget pressure variable had a negative and significant effect on ethical decision making of Tax Consultants in Bali Province, while work experience and professional commitment were both positively and significantly affected on ethical decision making of Tax Consultants in Bali Province.